PEMBERDAYAAN PETANI BAWANG MERAH DENGAN EFISIENSI PRODUKSI GUNA PENINGKATAN PENDAPATAN - Prabowo, Catur; Pelupessy, Ig. Henri; Fahlefi, Diva Riza; Harminingtyas, Rudika; Widowati, Maduretno (STIE Pelita Nusantara, 2025)
This community service program aims to empower shallot farmers in Brebes Regency by improving production efficiency to increase income and local economic sustainability. Brebes, a major national shallot production center, faces efficiency issues due to excessive input use and weak farm management. A team of lecturers conducted participatory training and mentoring covering technical efficiency, financial management, cost and revenue analysis, and strengthening farmer group institutions. The results showed an increase in productivity from 9.5 tons to 11.2 tons per hectare, a Revenue/Cost ratio from 1.42 to 1.68, and technical efficiency from 0.78 to 0.91. Awareness of financial recording increased from 15% to 85%, and a marketing cooperative was formed, strengthening farmers' bargaining power. This program successfully transformed traditional patterns into efficient and sustainable farming systems, while strengthening the role of universities in empowering agricultural communities.